Eat right for your inflammation type : the three-step program to strengthen immunity, heal chronic pain, and boost your energy - Berghoff, Maggie (Atria Books, 2021)
"Eat Right for Your Inflammation Type does for dangers of inflammation what Wheat Belly did for the hidden threats of gluten, targeting each cause of inflammation the same way Eat Right 4 Your Type did for blood type-specific health issues"--